2004
DOI: 10.1080/15017410409512653
|View full text |Cite
|
Sign up to set email alerts
|

Perceived participation. A comparison of students with disabilities and students without disabilities

Abstract: According to a recent study (Almqvist & Granlund, accepted)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 14 publications
1
45
0
4
Order By: Relevance
“…Previous studies have shown that school-aged children with disabilities often experience participation restrictions in the school (Eriksson et al, 2007), home, and community (Palisano et al, 2003;Murphy and Carbone, 2008;Galvin et al, 2010). Compared with school-aged children without disabilities, age-matched children with disabilities have lower levels of participation (Eriksson et al, 2007), and perceive that they have fewer school activities available to them (Eriksson, 2004;Lidström et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have shown that school-aged children with disabilities often experience participation restrictions in the school (Eriksson et al, 2007), home, and community (Palisano et al, 2003;Murphy and Carbone, 2008;Galvin et al, 2010). Compared with school-aged children without disabilities, age-matched children with disabilities have lower levels of participation (Eriksson et al, 2007), and perceive that they have fewer school activities available to them (Eriksson, 2004;Lidström et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…The result revealed a statistically significant correlation on the 1% level between ratings from the respondent groups for young children (only parents and professionals rated children) and children aged 7-12 years of age. For older children [13][14][15][16][17][18], the statistical correlation between the respondent group of children and the other two respondent groups was not significant. This indicates that it is important to ask teenagers themselves about their own perceptions of everyday life.…”
Section: Utility Of the Icf-cy For Documenting Child Characteristicsmentioning
confidence: 97%
“…Protocols used in data sets IV [13,[15][16][17][18]22], VII [14], VIII [24], IX [25], and X [26] also included sections to collect information that may be related to health and disability outcomes (i.e. diagnosis, age and gender) and reliability and validity of the instruments (i.e.…”
Section: Utility Of the Icf-cy For Documenting Child Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guthrie and Wigfield (2000) studied engagement and motivation in reading and concluded that engagement is strongly related to reading achievement. In a series of studies of engagement in school activities regarding children needing special support in Sweden, Granlund and associates (Eriksson & Granlund, 2004;Almquist & Granlund, 2005) reported that children's engagement in school is predicted by the children's self-rated autonomy and control perceptions. In a longitudinal study of students' engagement and school achievement, Skinner et al (1998) reported that students' control perceptions and engagement is related to how teachers attribute student achievement.…”
Section: Academic Achievement and Classroom Climatementioning
confidence: 98%